2017
DOI: 10.1111/nph.14459
|View full text |Cite
|
Sign up to set email alerts
|

Building a better foundation: improving root‐trait measurements to understand and model plant and ecosystem processes

Abstract: SummaryTrait-based approaches provide a useful framework to investigate plant strategies for resource acquisition, growth, and competition, as well as plant impacts on ecosystem processes. Despite significant progress capturing trait variation within and among stems and leaves, identification of trait syndromes within fine-root systems and between fine roots and other plant organs is limited. Here we discuss three underappreciated areas where focused measurements of fineroot traits can make significant contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
176
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 49 publications
2
176
0
1
Order By: Relevance
“…Global information on fine root traits is particularly important to advance our understanding and to predict plant and ecosystem processes under changing environmental conditions (McCormack et al, ). The fine root B/N ratio in forest ecosystems combines many important ecological processes including production, mortality, and decomposition of fine roots and can be served as a powerful metric for identifying the absorptive capacity of fine root systems (Persson & Stadenberg, ; Zang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Global information on fine root traits is particularly important to advance our understanding and to predict plant and ecosystem processes under changing environmental conditions (McCormack et al, ). The fine root B/N ratio in forest ecosystems combines many important ecological processes including production, mortality, and decomposition of fine roots and can be served as a powerful metric for identifying the absorptive capacity of fine root systems (Persson & Stadenberg, ; Zang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a global analysis of fine root traits, Iversen et al (2017) found that evergreen and deciduous broadleaf trees from temperate ecosystems had lower average C:N values when compared to needleleaf woody plants from the same ecosystem. It has been demonstrated that fine roots of deciduous tree species decompose more quickly than those of coniferous species (Mao et al 2011;Tong et al 2012).…”
Section: Root Traits and Plant Life Formmentioning
confidence: 99%
“…To predict how decomposition will respond to environmental changes, recent literature has emphasized the use of trait-based approaches and the need for measurements that directly connect fine root traits to forest C and nutrient cycling (Iversen et al 2017;McCormack et al 2017). Fine root chemical and morphological traits vary across ecosystems and plant taxa, which in turn influences rates of decay as litter quality is a product of both the chemistry and structure of decomposing tissues (Dornbush et al 2002;Birouste et al 2012;Prieto et al 2016).…”
Section: Root Traits and Plant Life Formmentioning
confidence: 99%
“…Particularly for studies that did not involve grasses, we found that TBCA tends to exceed RMF (log RMF/TBCA ratio <1) to greater degree in younger plants (<2 months). We hypothesize that this results from mass‐based root respiration rate declining as roots age (McCormack et al, ; Volder, Smart, Bloom, & Eissenstat, ). The overall lower root respiration rate of grasses (Tjoelker et al, ) may be why grasses as a group do not show the same ontogenetic trends in the RMF‐TBCA relationship as other species.…”
Section: Discussionmentioning
confidence: 97%